Scottmoria umbonata sp. nov. (Lecythidaceae) from Panama’s Caribbean rainforests - Batista-Guerra, Juvenal E.; Campos-Pineda, Ernesto; Carrión, Juan F. (Phytotaxa, 2026)
A new species, Scottmoria umbonata, from wet Caribbean forests on the slopes of Sierra Llorona, Province of Colón, Panama, is described and illustrated. We provide a comprehensive description of the new taxon, discuss its affinities with similar species, and include line drawings, field photographs, a distribution map, and a preliminary conservation status assessment.